A new name in Cymbidium (Orchidaceae) for one mistakenly published as a later homonym - Lan, Siren; Liu, Zhong-Jian (Phytotaxa, 2018)
A new specific name in Cymbidium (Orchidaceae), Cymbidium puerense, is here proposed for a rejected later homonym, Cymbidium densiflorum Liu & Lan (2018: 54), non Cymbidium densiflorum Griffith (1851: 337).